Is it Time to Consider the “Burnout Syndrome” A Distinct Illness? - Bianchi, Renzo; Schonfeld, Irvin Sam; Laurent, Eric (Frontiers in Public Health, 2015)
The “burnout syndrome” has been defined as a combination of emotional exhaustion, depersonalization, and reduced personal accomplishment caused by chronic occupational stress. Although there has been increasing medical interest in burnout over the last decades, it is argued in this paper that the syndrome cannot be elevated to the status of diagnostic category, based on (1) an analysis of the genesis of the burnout construct, (2) a review of the latest literature on burnout-depression overlap, (3) a questioning of the three-dimensional structure of the burnout syndrome, and (4) a critical examination of the notion that burnout is singularized by its job-related character. It turns out that the burnout construct is built on a fragile foundation, both from a clinical and a theoretical standpoint. The current state of science suggests that burnout is a form of depression rather than a differentiated type of pathology. The inclusion of burnout in future disorder classifications is therefore unwarranted. The focus of public health policies dedicated to the management of “burnout” should not be narrowed to the three definitional components of the syndrome but consider its depressive core.